2019
DOI: 10.1002/pca.2829
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and simultaneous quantitative determination of oligostilbenes in Paeonia ostii seed shell from different geographical areas in China and their comparative evaluation

Abstract: Introduction The Paeonia ostii T. Hong & J. X. Zhang seed shell, characterised by a high content of oligostilbenes, is one of the two most important by‐products in the preparation of seed oil. Oligostilbenes are considered characteristic constituents of the genus Paeonia, and can be used in fingerprinting to determine the geographical origin and the quality of raw materials. Objective To develop and optimise a simple and reproducible high‐performance liquid chromatography diode array detection (HPLC‐DAD) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…It was found that oligostilbenes existed in the seeds, mainly concentrated in the seeds shell of species of genus Paeonia [3] , [4] , [5] , [6] . The research of our research group found that the seeds shell of oil tree peony contained a variety of oligostilbenes, and these compounds were presented at high levels in the seeds shell of oil tree peony.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that oligostilbenes existed in the seeds, mainly concentrated in the seeds shell of species of genus Paeonia [3] , [4] , [5] , [6] . The research of our research group found that the seeds shell of oil tree peony contained a variety of oligostilbenes, and these compounds were presented at high levels in the seeds shell of oil tree peony.…”
Section: Introductionmentioning
confidence: 99%
“…The research of our research group found that the seeds shell of oil tree peony contained a variety of oligostilbenes, and these compounds were presented at high levels in the seeds shell of oil tree peony. Among them, SB, TV and TG had the highest content with important development and utilization value [3] , [7] , [8] . The bioactivities evaluation revealed that SB, TV and TG had good antioxidant [5] , antibacterial [9] , anti-inflammatory [10] , [11] , anti-tumor [4] , [9] , [12] , cognitive function improvement [13] , hypoglycemic effects [4] , enzyme inventory activity [4] , etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various phytochemicals, including phenolics [11,12], stilbenes [13], and terpenoids [14,15,16], were identified in tree peony in the previous studies. The phytochemical species and contents in tree peony differ according to the cultivars and organs involved [6,17,18,19].…”
Section: Introductionmentioning
confidence: 99%